2021
DOI: 10.7554/elife.62155
|View full text |Cite
|
Sign up to set email alerts
|

Abortive intussusceptive angiogenesis causes multi-cavernous vascular malformations

Abstract: Mosaic inactivation of CCM2 in humans causes cerebral cavernous malformations (CCMs) containing adjacent dilated blood-filled multi-cavernous lesions. We used CRISPR-Cas9 mutagenesis to induce mosaic inactivation of zebrafish ccm2 resulting in a novel lethal multi-cavernous lesion in the embryonic caudal venous plexus (CVP) caused by obstruction of blood flow by intraluminal pillars. These pillars mimic those that mediate intussusceptive angiogenesis; however, in contrast to the normal process, the pillars fai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
(79 reference statements)
1
11
0
Order By: Relevance
“…Finally, accumulating evidence implicates this transcription factor in vessel size regulation. Mammalian and piscine studies have found that mutations in Cerebral Cavernous Malformations (CCM) complex components and their partners induce pathogenic blood vessel dilations with elevated klf2 endothelial expression, and suppressing klf2 levels ameliorates these vascular lesions[34, 36, 37, 94-96]. Additionally, klf2a - and klf2a - ; klf2b -/+ fish mutants show axial vessels with progressively smaller outer diameters[35], consistent with the possibility that these animals have reduced vascular calibers.…”
Section: Resultsmentioning
confidence: 96%
“…Finally, accumulating evidence implicates this transcription factor in vessel size regulation. Mammalian and piscine studies have found that mutations in Cerebral Cavernous Malformations (CCM) complex components and their partners induce pathogenic blood vessel dilations with elevated klf2 endothelial expression, and suppressing klf2 levels ameliorates these vascular lesions[34, 36, 37, 94-96]. Additionally, klf2a - and klf2a - ; klf2b -/+ fish mutants show axial vessels with progressively smaller outer diameters[35], consistent with the possibility that these animals have reduced vascular calibers.…”
Section: Resultsmentioning
confidence: 96%
“…Inactivation of CCM genes leads to increased endothelial KLF2 expression 17, 18 , a transcription factor important in cavernoma formation 3, 19 . Nevertheless, silencing of adrb1 did not prevent the expected increased endothelial klf2a 17 expression in ccm2 morphant Tg(klf2a:H2b-EGFP) fish in which the nuclear EGFP expression is driven by the klf2a promoter (Figure 4A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Adult ccm2 CRISPR zebrafish display highly penetrant CCMs throughout the central nervous system 3 . Brains from adult ccm2 CRISPR fish on adrb1 -/- (12 brains) or wild type (13 brains) background were treated with CUBIC (clear, unobstructed brain/body imaging cocktails and computational analysis) 15 , and these transparent brains were then scanned with light-sheet microscopy and lesions were enumerated and volumes were estimated with NIH ImageJ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations